DIELECTRIC PARAMETERS OF DYED COTTON FABRICS - UMAR, ALHASSAN HARUNA; MUHAMMAD, AMINU TUKUR (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2021)
Non-contact electrodes have capacities in long-term monitoring of electrocardiogram (ECG) and early detection of heart abnormalities. In non-contact ECG sensing, the dielectric materials strongly influence the effectiveness of the electrodes. Over the past three decades, there has been extensive research on fabric dielectrics because they are harmless, plentiful, comfortable, and skin conformable. A high and stable permittivity is essential in fabric dielectrics used in noncontact electrodes. However, the dye used on fabrics can immensely influence their relative permittivity and electrode coupling capacitance. This study investigates the effects of dye on dielectric parameters of cotton fabrics using the parallel plate technique in dry and moisturized conditions. The results show that undyed fabric has higher capacitance but lower relative permittivity in dry and moisturized conditions. In contrast, dyed fabrics showed higher permittivity, but slight differences were found depending on the dye used. These findings demonstrate that dyed fabrics are more effective as dielectrics for capacitive ECG electrodes.